Pelatihan Membuat Vertical Composter Garden untuk Mengatasi Sampah Organik dan Ketahanan Pangan Keluarga - Indah Karina Yulina; Tania Avianda Gusman; Yayan Hendriyan; Dewi Nurdiyanti; Hunaeni Hunaeni; Khometa Pawangsari (Institut Pertanian Bogor, 2026)
One of the ways to reduce greenhouse gases can be done through waste management from the source, because organic waste is one of the sources of methane gas that causes the greenhouse effect. The lack of education at the community level about efforts to reduce waste thrown away by processing waste is one of the causes of waste accumulation in landfills. This research aims to train the community to make an independent Vertical Composter Garden (VCG) in order to reduce organic waste in their area. The training was held in Cengkuang Village, Palimanan District, with a total of 16 participants. The method used is periodic training and mentoring followed by a final evaluation. The result obtained was that the level of understanding of participants increased after being given an explanation of waste management materials and how to make VCGs. The planting period depends on the type of plant. The fastest harvest period is only 14 days for chives, while the longest is for chili plants, which takes about 3.5 months from seeding to harvest.